Hepatic flares promote rapid decline of serum hepatitis B surface antigen (HBsAg) in patients with HBsAg seroclearance: A long‐term follow‐up study. Issue 3 (25th May 2015) - Nagaoka, Shinya; Abiru, Seigo; Komori, Atsumasa; Sasaki, Ryu; Bekki, Shigemune; Hashimoto, Satoru; Saeki, Akira; Yamasaki, Kazumi; Migita, Kiyoshi; Nakamura, Minoru; Ezaki, Hironori; Yatsuhashi, Hiroshi
Abstract : Aim: Serum hepatitis B surface antigen (HBsAg) seroclearance is one of the ultimate goals of management of chronic hepatitis B. We investigated the kinetics of serum HBsAg before HBsAg seroclearance in patients with chronic hepatitis B. Methods: We retrospectively analyzed 392 Japanese chronic hepatitis B patients who had been followed for 5 years or more between 1980 and 2000. Serum HBsAg levels were measured annually using chemiluminescent enzyme immunoassay. Results: During a median follow up of 14 years, 50 patients demonstrated HBsAg seroclearance (annual incidence rate, 0.91%). Multivariate analysis with baseline characteristics revealed that HBsAg of less than 3.3 log IU/mL (hazard ratio [HR], 2.22; P  = 0.008) and treatment with nucleoside/nucleotide analog (HR, 0.12; P  = 0.001) were independent predictive factors for seroclearance. The median HBsAg levels at 20, 10, 5, 3 and 1 year prior to seroclearance were 3.89, 2.84, 1.84, 0.78 and −1.10 log IU/mL, respectively. The rapid decline group, comprising patients who achieved HBsAg seroclearance within 5 years after confirmed HBsAg levels of 2 log IU/mL, demonstrated: (i) high alanine aminotransferase (ALT) levels; and (ii) a low frequency of liver cirrhosis progression. A significant reduction in annual HBsAg levels was found in years marked by at least one ALT flare (ALT ≥200 IU/L) (flare [+], n  = 62) than in those without (flare [−], n  = 323) (0.29 vs 0.17 log IU/mL/year, P  = 0.003). Conclusion: Hepatic flares promoted rapid declines and greater annual reductions of HBsAg levels in patients with HBsAg seroclearance.